Practicality of popular scientific books on herbs of Tabanio coastal forest, Tanah Laut Regency, Indonesia - Rakhmani Mulkan; Mochamad Arief Soendjoto; Dharmono Dharmono (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2022)
A Popular Scientific Book (PSB), which mainly contains 12 species of herbs that grow in the Tabanio Coastal Forest, Tanah Laut Regency, has been compiled, but its practicality has not been determined. The research aims to determine the practicality of the book. The determination is based on the results of the readability test, implementation, and response to the PSB. The subject is a student who has taken a course in Higher Plant Botany (Phanerogamae). Readability was tested one on one by three subjects. Implementation was observed by 5 observers who assessed implementation by small groups (5 subjects) and also by field groups (10 subjects). The instrument is a questionnaire with 9 statements. Responses to PSB were also obtained from small groups consisting of 5 subjects and field groups with 10 subjects. The questionnaire instrument consists of 15 statements. The readability value is 94.23% or categorized as Very Good. The value of the implementation of expectations originating from the small group is 91.11% and the actual implementation of the field group is 92.22%. These two values are categorized as Very Good and seem steady. Expected response values and actual responses are 87.20% and 88.40%, respectively. Both of these response values are categorized as Strongly Agree and also steady. Based on the test results, overall this PSB is practically used with the consideration that any deficiencies found are always revised.Abstrak Buku Ilmiah Popular (BIP) yang konten utamanya 12 spesies herba yang tumbuh di Hutan Pantai Tabanio, Kabupaten Tanah Laut sudah disusun, tetapi kepraktisannya belum ditentukan. Penelitian bertujuan untuk menentukan kepraktisan buku tersebut. Penentuannya berdasarkan pada hasil uji keterbacaan, keterlaksanaan, dan respons terhadap BIP. Subjeknya adalah mahasiswa yang pernah mengambil mata kuliah Botani Tumbuhan Tinggi (Phanerogamae). Keterbacaan diuji satu lawan satu oleh tiga subjek. Keterlaksanaan diamati oleh 5 pengamat yang menilai pelaksanaan oleh kelompok kecil (5 subjek) dan juga oleh kelompok lapangan (10 subjek). Instrumennya berupa angket dengan 9 pernyataan. Respons terhadap BIP diperoleh juga dari kelompok kecil yang terdiri atas 5 subjek dan kelompok lapangan dengan 10 subjek. Instrumen angketnya terdiri atas 15 pernyataan. Nilai keterbacaan adalah 94,23% atau terkategori Sangat Baik. Nilai keterlaksanaan harapan yang bersumber dari kelompok kecil adalah 91,11% dan keterlaksanaan aktual dari kelompok lapangan 92,22%. Kedua nilai ini dikategorikan Sangat Baik dan terkesan ajeg. Nilai respons harapan dan respons aktual berturut-turut adalah 87,20% dan 88,40%. Kedua nilai respons ini terkategori Sangat Setuju dan juga bersifat ajeg. Berdasarkan pada hasil uji itu, secara keseluruhan BIP ini praktis digunakan dengan pertimbangan bahwa segala kekurangan yang ditemukan selalu direvisi.